Anti-inflammatory phomalichenones from an endolichenic fungus Phoma sp. (August 2018) - Kim, Jong; Ko, Wonmin; Kim, Eun; Kim, Gil; Hwang, Gwi; Son, Sangkeun; Jeong, Min-Hye; Hur, Jae-Seoun; Oh, Hyuncheol; Ko, Sung-Kyun; Jang, Jae-Hyuk; Ahn, Jong
Abstract Four new compounds, phomalichenones A–D (1 –4 ), and seven known compounds (5 –11 ) were isolated from the cultures of an endolichenic fungusPhoma sp. EL002650. Their structures were determined by the analysis of their spectroscopic data (NMR and MS). Compounds1 and6 inhibited nitric oxide (NO) production in lipopolysaccharide (LPS)-stimulated RAW264.7 macrophages. In addition, compound1 diminished the protein expression levels of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2), and decreased the mRNA expression levels of pro-inflammatory cytokines, such as tumor necrosis factor-α (TNF-α ), interleukin(IL)-1β, and IL-6.